Optimization design and experiment on ripple surface type pickup finger of precision maize seed metering device - Jinwu, Wang; Han, Tang; Jinfeng, Wang; Xin, Li; Huinan, Huang (International Journal of Agricultural and Biological Engineering, 2017)
A ripple surface type pickup finger was designed to improve the performance of pickup finger precision maize seed metering device and to provide a solution for maize precision planter. The main structure and working principle of seed metering device were detailed in this paper. The dimension size distributions of maize seeds in different types were studied, the gestures of seeds clamped by pickup finger were analyzed, and the clamping dynamical model of pickup finger was established by theoretical analysis. To optimize the structural parameters of ripple surface type pickup finger, the discrete element method (DEM) model of pickup finger precision maize seed metering device was established by the discrete element software EDEM. The numerical simulations of orthogonal seeding performance experiments were conducted to analyze the influences of these factors on the quality of seeding. The rotational speed, wavelength of ripple surface and amplitude of ripple surface were selected as the experimental factors. The average seeding qualified index and the average seeding coefficient of variation on four different types of maize seeds were chosen for evaluating the seeding performance. The results showed that, the average seeding qualified index was 93.35% and the average seeding coefficient of variation was 11.23% under conditions of the 25 r/min rotational speed, 8 mm wavelength of ripple surface and 2 mm amplitude of ripple surface. Under the same condition, the bench test was done which showed that the results of test and simulation were consistent. The maximum error of qualified index was 1.95% and the qualified index of improved seed metering device exceeded the original one by 12.34%. The working performance can meet the requirements of precision maize seeding. Keywords: precision maize planter, seed metering device, pickup finger, ripple surface DOI: 10.3965/j.ijabe.20171001.2050 Citation: Wang J W, Tang H, Wang J F, Li X, Huang H N. Optimization design and experiment on ripple surface type pickup finger of precision maize seed metering device. Int J Agric & Biol Eng, 2017; 10(1): 61－71.